Sterol methyltransferase is required for optimal mitochondrial function and virulence in Leishmania major. Issue 1 (21st October 2018) - Mukherjee, Sumit; Xu, Wei; Hsu, Fong‐Fu; Patel, Jigesh; Huang, Juyang; Zhang, Kai
Summary: Limited knowledge on the exact functions of ergostane‐based sterols has hampered the application of sterol synthesis inhibitors against trypanosomatid parasites. Sterol methyltransferase (SMT) is directly involved in the synthesis of parasite‐specific C24‐methylated sterols, including ergosterol and 5‐dehydroepisterol. While pharmacological studies hint at its potential as a drug target against trypanosomatids, direct evidence for the cellular function and essentiality of SMT is lacking. Here, we characterized the SMT knockout mutants and their complemented strains in Leishmania major, the causative agent for cutaneous leishmaniasis. Deletion of SMT alleles led to a complete loss of C24‐methylated sterols, which were replaced by cholestane‐based sterols. SMT‐null mutants were fully viable and replicative in culture but showed increased sensitivity to sphingolipid synthesis inhibition. They were not particularly vulnerable to heat, acidic pH, nitrosative or oxidative stress, yet exhibited high mitochondrial membrane potential and increased superoxide generation indicating altered physiology of the mitochondria. Despite possessing high levels of GPI‐anchored glycoconjugates, SMT‐null mutants showed significantly attenuated virulence in mice. In total, our study reveals that the biosynthesis of ergostane‐based sterols is crucial for the proper function of mitochondria and the proliferation of Leishmania parasites in mammals. Abstract : Sterol methyltransferase (SMT) catalyzes the transfer of a methyl group from S ‐adenosine‐methionine to the C24 position of the sterol side chain. In Leishmania major, SMT‐null mutants cannot synthesize ergosterol or ergosterol‐like sterols but are fully viable in culture. However, SMT is required for the maintenance of mitochondrial membrane potential, ROS production and parasite virulence.